The importance of cytoplasmic strings during early human embryonic development - Joo, Kata; Nemes, Annamaria; Dudas, Beata; Berkes-Bara, Eva; Murber, Akos; Urbancsek, Janos; Fancsovits, Peter (Frontiers in Cell and Developmental Biology, 2023)
Objectives: During human in vitro fertilisation (IVF) treatments embryologist try to select the most viable embryos for transfer (ET). Previously, embryos were evaluated on the basis of light microscopic morphological parameters. However, this is currently accomplished by morphokinetic analysis of time-lapse recordings. This technique provides us the opportunity to observe cytoplasmic strings at the blastocyst stage. The aim of this work was to examine the relation between the presence of cytoplasmic strings (CS) and the embryo viability in human in vitro fertilised embryos.IVF treatments performed at the Division of Assisted Reproduction between December 2020 and March 2021. The dynamics of embryo development, embryo morphology and morphokinetic scores generated by a time-laps system was compared between the presence of cytoplasmic strings (CS+) and its absence (CS-) at blastocyst stage.The development of 208 embryos from 78 patient were examined. 81.2% of the embryos had CS in blastocyst stage. Embryos created by conventional IVF had 77%, while embryos fertilised by intracytoplasmic sperm injection (ICSI) had 86% of CS presence (p=0.08). CS+ embryos developed in a greater number into a higher quality blastocyst (52.1% vs 20.5%, p= 0,02). The This is a provisional file, not the final typeset article morphokinetic score values characterizing the development of embryos as KIDScore (Known Implantation Data) and iDAScore (Intelligent Data Analysis),which were higher in CS+ groups (KID: 6.1±2.1 vs 4,7±2,07;iDA 8.0±1.9 vs 6.8±2.3, p <0.01) The dynamic of the early embryo development was similar between the two groups, however, CS+ embryos reached blastocyst stage significantly earlier (tB: 103.9 hours vs. tB: 107.6 hours; p=0.001).Conclusions: Based on our results, there was a higher number of embryos with cytoplasmic strings than without, and its presence is not related to the fertilisation method. These embryos developed faster into a blastocyst stage and their morphokinetic (KIDScore and iDAScore) parameters were better. All these results suggest that the presence of CS indicates a higher embryo viability. The examination of this feature may help us to make decisions about the embryos with higher implantation potential.